Interactive Media Based on Adobe Animate CC Increases Student Participation in History Learning - Orbit Thomas; Nani Setiawati; Rahman; Store; Alexandro, Rinto; Wibowo (LPPM Undiksha, 2024)
In the learning process, teachers still use lecture and discussion methods. Apart from that, the lack of multimedia-based teaching materials affects the level of student participation. This has an impact on low student learning outcomes. This research aims to analyze the influence of using interactive media based on Adobe Animate CC on student participation in history learning. This research is quantitative research with a descriptive analysis approach assisted by SPSS. The population in this study consisted of students in classes XI-1, XI-2, and XI-3, totaling 97 students. The entire population was used as the sample in this study. Data collection techniques in this research were through questionnaires, observation, documentation, and tests. The data collection instrument is a questionnaire sheet. The data analysis technique uses inferential statistical analysis. The results of this research indicate that the variable use of interactive media based on Adobe Animate CC has a significant influence on the variable of student participation in history learning. The main results of this research prove that the use of Adobe Animate CC interactive media is very suitable for teachers to apply continuously in history learning because it can have a good impact on students, thereby increasing student participation in learning. The research implication is that the use of interactive media can increase students' interest and motivation in learning history, changing learning that is often considered boring into a more exciting and interactive experience.